No clear evidence for correlations between handgrip strength and sexually dimorphic acoustic properties of voices. Issue 6 (24th September 2018) - Han, Chengyang; Wang, Hongyi; Fasolt, Vanessa; Hahn, Amanda C; Holzleitner, Iris J; Lao, Junpeng; DeBruine, Lisa M; Feinberg, David R; Jones, Benedict C
Abstract: Objectives: Recent research on the signal value of masculine physical characteristics in men has focused on the possibility that such characteristics are valid cues of physical strength. However, evidence that sexually dimorphic vocal characteristics are correlated with physical strength is equivocal. Consequently, we undertook a further test for possible relationships between physical strength and masculine vocal characteristics. Methods: We tested the putative relationships between White UK ( N = 115) and Chinese ( N = 106) participants' handgrip strength (a widely used proxy for general upper‐body strength) and five sexually dimorphic acoustic properties of voices: fundamental frequency (F0), fundamental frequency's SD (F0‐SD), formant dispersion (Df), formant position (Pf), and estimated vocal‐tract length (VTL). Results: Analyses revealed no clear evidence that stronger individuals had more masculine voices. Conclusions: Our results do not support the hypothesis that masculine vocal characteristics are a valid cue of physical strength.